Hubungan Kepekaan Serta Ketanggapan Pengasuhan Ibu Terhadap Perkembangan Anak Prasekolah - Noordiati Mohammad Hakimi, Tunjung Wibowo (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Sensitivity and Responsiveness of Mothers’ Parenting InfluenceThe Preschool Child DevelopmentBackground: It is estimate that more than 200 million children in developing countries are exposed to risk for poverty, malnutrition, poor health and lack of stimulation in the home environment that influence the failure of their optimum development. Sensitivity and responsiveness of mothers’ parenting are major factors for the achievement of their children neurophysiological, physical and psychological development of children and major representation of parenting behavior related to positive development and child health in the future.Objective: To know sensitivity and responsiveness of mothers’ parenting influenced the preschool child development at Subdistrict of Pahandut Palangkaraya.Methods: A cross sectional study was done towards 143 mothers’ and 60-72 months children from 12 kindergarten at subdistrict of Pahandut Palangkaraya using proportional random sampling. The study was analyzed using bivariate (chi square test).Results: The result of the analysis showed sensitivity and responsiveness of mothers’ parenting showed significant association with child development. Child who have mothers’ parenting with hingh sensitivity and responsiveness that have 1.8 time greather than for not development delay.Conclusion: Sensitivity and responsiveness of mothers’ rearing were associated with child development and health. Increasing sensitivity and responsiveness of mothers’ rearing such as increased interaction of mothers and children, development stimulation, supportive home environment, child care and nutrition fulfillment would help children achieve optimum development potential.Keywords: sensitivity, responsiveness, child development, mothers’ parenting, preschool children